2019
DOI: 10.1016/j.soscij.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

I know people who can and who cannot: A measure of the perception of economic inequality in everyday life

Abstract: This paper describes the development of the Perceived Economic Inequality in Everyday Life (PEIEL) scale. It is written and validated in Spanish. We first carried out an exploratory study, using a sample of 205 participants (52.2% men and 47.8% women; age: M = 24.69, SD = 8.95). We then conducted a confirmatory study with a sample size of 215 individuals (43.7% men and 56.3% women; age: M = 23.83, SD = 6.46). Results showed that the PEIEL scale is a valid and reliable unidimensional instrument. This scale nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 53 publications
3
50
0
10
Order By: Relevance
“…Furthermore, this result supports previous studies that found that there is a negative relationship between perceived economic inequality and tolerance to economic inequality (Castillo et al, 2012;García-Castro et al, 2019;Khun, 2019) in contrast to studies suggesting the opposite (Loveless, 2013;Trump, 2018).…”
Section: Effects On Inequality Intolerancesupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, this result supports previous studies that found that there is a negative relationship between perceived economic inequality and tolerance to economic inequality (Castillo et al, 2012;García-Castro et al, 2019;Khun, 2019) in contrast to studies suggesting the opposite (Loveless, 2013;Trump, 2018).…”
Section: Effects On Inequality Intolerancesupporting
confidence: 90%
“…Despite these findings, the opposite has also been suggested in previous research (Loveless, 2013;Trump, 2018). In a previous study, measuring perceived inequality based on the closest context, PEIEL positively predicted intolerance toward inequality over and above the most popular measures of general perception of inequality used in the literature (García-Castro et al, 2019).…”
Section: Perceived Economic Inequality In Everyday Life Tolerance Tomentioning
confidence: 65%
See 3 more Smart Citations